Using circular economy principles to recycle materials in guiding the design of a wet scrubber-reactor for indoor air disinfection from coronavirus and other pathogens - Shishkin, Andrei; Goel, Gaurav; Baronins, Janis; Hoskins, Clare; Goel, Saurav (Elsevier, 2021)
An arduous need exists to discover rapid solutions to avoid the accelerated spread of coronavirus especially through the indoor environments like offices, hospitals, and airports. One such measure could be to disinfect the air, especially in indoor environments. The goal of this work is to propose a novel design of a wet scrubber-reactor to deactivate airborne microbes using circular economy principles. Based on Fenton’s reaction mechanism, the system proposed here will deactivate airborne microbes (bioaerosols) such as SARS-CoV-2. The proposed design relies on using a highly porous clay-glass open-cell structure as an easily reproducible and cheap material. The principle behind this technique is an in-situ decomposition of hydrogen peroxide into highly reactive oxygen species and free radicals. The high porosity of a tailored ceramic structure provides a high contact area between atomized oxygen, free radicals and supplied polluted air. The design is shown to comply with the needs of achieving sustainable development goals.
Keywords: COVID-19; Porous ceramics; Preparedness; Coronavirus; Scrubber-reactor; Air disinfection